1992
DOI: 10.1007/bf01245361
|View full text |Cite
|
Sign up to set email alerts
|

In vivo trapping of hydroxyl free radicals in the striatum utilizing intracranial microdialysis perfusion of salicylate: effects of MPTP, MPDP+, and MPP+

Abstract: Increased formation of hydroxyl free radicals (.OH) reflected by .OH adduct of salicylate in brain dialysate was demonstrated during the sustained (more than 2 hours) dopamine overflow elicited by 75 nmol of 1-methyl-4-phenyldihydropyridine (MPDP+) and 1-methyl-4-phenylpyridinium (MPP+) in the rat striatum. Owing to its weak dopamine releasing action, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) did not significantly increase the .OH formation. This data suggests that sustained elevation of dopamine in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…Several of these compounds can also inhibit Complex I, further affecting energy impairment (67). Although the present studies have emphasized the role of intracellular DA in neurotoxicity, in vivo studies have established that MPP ϩ -mediated efflux of DA also generates extracellular hydroxyl radicals (17). Indeed, DA can be toxic both in vitro (31,73) and in vivo (74,75).…”
Section: Role Of Dopamine In Mppmentioning
confidence: 82%
See 1 more Smart Citation
“…Several of these compounds can also inhibit Complex I, further affecting energy impairment (67). Although the present studies have emphasized the role of intracellular DA in neurotoxicity, in vivo studies have established that MPP ϩ -mediated efflux of DA also generates extracellular hydroxyl radicals (17). Indeed, DA can be toxic both in vitro (31,73) and in vivo (74,75).…”
Section: Role Of Dopamine In Mppmentioning
confidence: 82%
“…However, MPP ϩ does affect other processes. For example, MPP ϩ rapidly induces DA release and subsequent formation of hydroxyl radicals both in vivo and in vitro (12)(13)(14)(15)(16)(17). Because the timing of this process is comparable with exocytosis (18), the deleterious effects of extracellular DA oxidation may actually precede mitochondrial dysfunction, which occurs more slowly (6,19).…”
mentioning
confidence: 99%
“…Obata and Chiueh (1992) have used the technique of microdialysis to demonstrate in vivo that MPDP + (1-methyl-4-phenyl-2,3-dihydropyridinium ion, a further MPTP metabolite) as well as MPP + on intrastriatal application are briefly able to potentiate dopamine liberation from dopaminergic neurons in the rat, and indirectly that there was a brief production of hydroxyl free radicals, as evidenced by the reaction products formed with salicylic acid. In in vitro investigations using ESR (electron spin resonance) spectroscopy it could be shown that superoxide free radicals are formed during the metabolism of MPTP (e.g.…”
Section: The Mechanism Of the Neurotoxic Actionmentioning
confidence: 99%
“…and MPP ϩ (3). MPTPinduced hydroxyl radical formation in the striatum and substantia nigra of the mouse has been shown in vivo (4); in addition, MPP ϩ alone promotes reactive oxygen species (ROS) formation (5)(6)(7).…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%